1993
DOI: 10.1007/bf00011058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rootstock on the occurrence of lime-induced chlorosis of potted Vitis vinifera L. cv. ?Pinot blanc?

Abstract: The chlorosis susceptible Vitis vinifera L. cv. 'Pinot blanc' was grafted on two hybrid rootstocks with different iron efficiency, as follows: V. Berlandieri × V. rupestrb '140 Ru' (iron-efficient) and V. riparia × V. rupestris '101-14' (iron-inefficient). The grafted vines were grown in pots of a calcareous and a non-calcareous soil. The shoot growth was periodically checked and leaves, selected at two different times (at the middle of the annual growing period), were assayed for total chlorophyll, ferrous ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…However, plant growth of TN11.11 was less affected by Fe deficiency compared to that of TN8.7, suggesting a relatively greater tolerance of TN11.11 to such constraint. Moreover, the increase in root biomass shown by TN11.11 plants grown under Fe deficiency is a response already described for tolerant genotypes (Marschner et al 1996;Pestana et al 2005), and often associated with an increased number of secondary and tertiary roots (Bavaresco et al 1994), leading to a more efficient exploration of the soil. Under lime-induced Fe deficient conditions, Fe concentration in the shoots of both lines was more depressed than in the absence of Fe.…”
Section: Genotypic Variation In Response To Fe Deficiency and Comparimentioning
confidence: 97%
“…However, plant growth of TN11.11 was less affected by Fe deficiency compared to that of TN8.7, suggesting a relatively greater tolerance of TN11.11 to such constraint. Moreover, the increase in root biomass shown by TN11.11 plants grown under Fe deficiency is a response already described for tolerant genotypes (Marschner et al 1996;Pestana et al 2005), and often associated with an increased number of secondary and tertiary roots (Bavaresco et al 1994), leading to a more efficient exploration of the soil. Under lime-induced Fe deficient conditions, Fe concentration in the shoots of both lines was more depressed than in the absence of Fe.…”
Section: Genotypic Variation In Response To Fe Deficiency and Comparimentioning
confidence: 97%
“…This evaluation can be performed also in vitro on a medium containing a high level of bicarbonates (Bavaresco et al, 1993). The identification of real causes of the occurrence of the lime-induced chlorosis under conditions of a given vineyard is very important for the improvement and/or elimination of these biotic stress situations.…”
Section: Causes Of the Occurrence Of Lime-induced Chlorosismentioning
confidence: 99%
“…According to the growth rate of sink tissues and such organs as the roots, shoot apex, fruits and storage organs can be limited by supply of photosynthates from the source leaves or by a limited capacity of the sink to utilize the photosynthates (Marschner, 1995). In some cases, lime-induced chlorosis is related to a low Fe uptake and its translocation to leaves (Bavaresco et al, 1992), in others to a high content of Fe in leaves, which has to be somehow inactivated (Mengel, Breininget, Bübl, 1984;Bavaresco et al, 1993).…”
Section: Causes Of the Occurrence Of Lime-induced Chlorosismentioning
confidence: 99%
“…For example, Bavaresco and Lovisolo (2000) showed that different scion/rootstock combinations among three Pinot blanc cultivars and two rootstocks (SO4 and 3309C) lead up to different results in response to iron chlorosis, strongly related to the chlorophyll content and vegetative growth which were correlated with specific conductivity in scion/rootstock surface. In another work, Bavaresco, Fraschini, & Perino (1993) compared the response of 140 Ruggeri and 101-14 rootstocks to iron chlorosis showing that the iron-efficient rootstock (140 Ruggeri) did not induce chlorosis when growing on the calcareous soil, while the opposite occurred with the iron-inefficient rootstock (101-14). Ksouri, M'rah, Gharsalli, & Lachaâl (2006) found that the high tolerance of 140 Ruggeri to Fe-chlorosis is partially due to its high root Fe(III)-reductase activity and the ability of this rootstock to release phenolic compounds in the medium (Ksouri et al, 2006).…”
Section: Introductionmentioning
confidence: 99%